2020
DOI: 10.1002/lary.29033
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With the Choice of Radiation Therapy Treatment Facility in Head and Neck Cancer

Abstract: Objective To analyze the clinicodemographic characteristics and treatment outcomes of patients receiving postoperative radiation therapy (PORT) at a different treatment facility rather than the initial surgical facility for head and neck cancer. Study Design: Retrospective cohort analysis. Methods Utilizing the National Cancer Data Base, 2004 to 2015, patients with a diagnosis of oral cavity/oropharyngeal, hypopharyngeal, and laryngeal squamous cell carcinoma were studied. Multivariate analysis was completed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 22 publications
0
19
1
Order By: Relevance
“…Kaplan‐Meier analyses showed that patients undergoing PORT at a different facility for SNSCC did not have significantly different OS compared with patients undergoing PORT at the same facility. This is in contrast to previous studies of NSN‐HNC patients, which showed significantly lower survival for those undergoing PORT at a different facility 3,8 . There are potential barriers in communication between providers at different facilities treating HNC patients, but the integration of electronic medical records systems has been shown to decrease the fragmentation of care 9,10 …”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Kaplan‐Meier analyses showed that patients undergoing PORT at a different facility for SNSCC did not have significantly different OS compared with patients undergoing PORT at the same facility. This is in contrast to previous studies of NSN‐HNC patients, which showed significantly lower survival for those undergoing PORT at a different facility 3,8 . There are potential barriers in communication between providers at different facilities treating HNC patients, but the integration of electronic medical records systems has been shown to decrease the fragmentation of care 9,10 …”
Section: Discussionmentioning
confidence: 73%
“…This is in contrast to previous studies of NSN-HNC patients, which showed significantly lower survival for those undergoing PORT at a different facility. 3,8 There are potential barriers in communication between providers at different facilities treating HNC patients, but the integration of electronic medical records systems has been shown to decrease the fragmentation of care. Limitations of this study include miscoding of entries in the NCDB and the lack of details with regard to recurrence, treatment-specific outcomes, disease-specific survival, facility reputation, and patient traveling constraints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not explicitly applying the social-ecological framework, prior studies have considered individual-level factors and added a level to the framework, with organization-level factors increasing risk of PORT delay. Specifically, authors include payers, separate surgical and PORT facilities, postoperative length of stay, advanced stage at presentation, and tumor site . Contrary to these prior investigations, the current study assessed the individual- and community-level influences on delays and found that a predictive model incorporating multiple levels of influence from the social-ecological framework outperformed a model based on individual-level factors alone.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic factors such as race, ethnicity, sex, and insurance status have previously been implicated in LSCC incidence and management disparities. 10,39,[46][47][48][49] Non-White race has been shown to be an independent risk factor for laryngeal cancer prognosis regardless of age, sex, tumor size, and nodal invasion, demonstrating a reduced 5-year survival rate in Hispanic and Black populations as compared with White populations (59.5%, 52.7%, and 60.6%, respectively). 10 Lebo et al 50 reported that insurance, Black race, female sex, and older age are associated with LSCC severity at presentation, with lack of insurance being the strongest predictor.…”
Section: Discussionmentioning
confidence: 99%